TEACHER’S SENSE OF SELF-EFFICACY TO PROBLEM BEHAVIOR AND THE ROLE OF ORGANIZATION CLIMATE IN REFERRAL AND REMOVAL (Proceedings of International Conference on Special Education, 2017)
Problem Behavior among young children in early childhood education centers are found to be at a growing rate from the literature. Problem behaviors if left untreated may lead to more severe outcomes for some children. Problem behaviors pose by young children in the early childhood classroom interrupt with classroom instruction. Early Identification which directs to early intervention is an evident based method to treat children at-risk of behavioral issues. Early intervention prepares children at-risk by providing an effective positive behavior support that may reduce the option of special education referral and removal from the mainstream environment. However problem behaviors in the early childhood classroom is remain under recognized or not widely addressed. Literature reports that, teachers due to their workload may delay the referral and when they are unable to handle the problem behaviors, removal will be the short-term solution.. This study surveys preschool teachers working in the Permata Negara Centers in Peninsular Malaysia to examine teachers’ sense of self- efficacy to problem behavior. Specifically, the study address teachers beliefs on their competency in handling problem behavior, the kind of support they receive from their organization committee, how useful are those support to address problem behaviors and the referral and removal consequences. Teachers will be given a combination of three Likert scale questionnaires’ to be rated online. Teachers’ Self-Efficacy, Early Childhood Job Satisfaction Survey (ECJSS) and Working with Challenging Behavior Preschool Survey (WCBPS), these three instruments was adapted to answer 8 research questions and 8 hypothesis, predicted from the literature review. The data analysis method will be descriptive analysis and multiple regression analysis. The findings of the study is expected to be generalized to other early childhood care and education centers in the government and private sectors in Malaysia